(untitled) (LACCEI, 2024)
This study aims to establish the relationship between instrumental digital competencies and virtual education in times of covid-19. Its approach is quantitative, descriptive, correlational, and cross-sectional. The population consisted of 5940 students from 7 faculties of a public university in Lima, distributed in 53 study programs of the 2021-I academic cycle. A representative probability sample of 360 was established. The results indicate that at higher levels of didactic digital skills of the teacher, there will be higher levels of virtual education received, which indicates that there is an effective and relevant management of various technological resources and methodological strategies in class sessions this will have an effect on improving the experience of students in virtual environments and is a factor that guarantees the teaching process However, not all teachers are perceived as having these skills, since in the survey applied 66.7% (240) of the students consider the teachers’ digital didactic skills to be regular and the rest deficient and none efficient.